2019
DOI: 10.1021/acs.jpclett.9b00810
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Structural Change upon S1–T1 Conversion Assists the Thermally Activated Delayed Fluorescence Process in Carbazole-Benzonitrile Derivatives

Abstract: Thermally activated delayed fluorescence (TADF) molecules are gathering attention for their potential to boost the efficiency of organic light-emitting diodes without precious metals. Minimizing the energy difference between the S 1 and T 1 states (ΔE ST ) is a fundamental strategy to accelerate reverse intersystem crossing (RISC). However, the lack of microscopic understanding of the process prevents adequate design strategies for efficient TADF materials. Here, we focused on four carbazole-benzonitrile (Cz-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 30 publications
6
62
1
Order By: Relevance
“…In this regard, OLEDs fabricated with Au I and Au III ‐TADF emitters ( τ <2 μs) have achieved small roll‐off (<10 %) . A recent study suggested that improving the rigidity of emitters could suppress the structural deformation upon S 1 –T 1 transformation thereby reducing the activation energy barrier for reverse intersystem crossing (RISC) and leading to efficient TADF . It is thus conceived that Au III complexes supported by trianionic tetradentate ligands (e.g.…”
Section: Introductionsupporting
confidence: 52%
“…In this regard, OLEDs fabricated with Au I and Au III ‐TADF emitters ( τ <2 μs) have achieved small roll‐off (<10 %) . A recent study suggested that improving the rigidity of emitters could suppress the structural deformation upon S 1 –T 1 transformation thereby reducing the activation energy barrier for reverse intersystem crossing (RISC) and leading to efficient TADF . It is thus conceived that Au III complexes supported by trianionic tetradentate ligands (e.g.…”
Section: Introductionsupporting
confidence: 52%
“…The spectral changes are similar to the trend in the THF solution reported in our previous report. 11 Because TR-IR in the region is sensitive to intramolecular charge transfer and distortion of molecular geometry 11 , this spectral change suggests a structural change associated with the ISC from S1 to T1. Although infrared spectral peaks of a specific functional group often change depending on solvents 18,19 , the IR stretching bands of o-3CzBN in the 1100-1700 cm −1 region were independent of the solvent polarity, indicating investigated in a previous report and correlated well to the experimentally observed spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Although infrared spectral peaks of a specific functional group often change depending on solvents 18,19 , the IR stretching bands of o-3CzBN in the 1100-1700 cm −1 region were independent of the solvent polarity, indicating investigated in a previous report and correlated well to the experimentally observed spectra. 11 Here, we examined the S1 state spectra of o-3CzBN in toluene and MeCN solvents, by conducting similar calculations to simulate vibrational spectra ( Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations